Availability of essential, generic medicines before and during COVID-19 at selected public pharmaceutical supply agencies in Ethiopia: a comparative cross-sectional study - Mohammed Mecha; Zeleke Mekonnen; Tsegaye Melaku; Gudina Terefe Tucho; Christine Årdal; Marianne Jahre (BMJ Open)
Objectives Lockdowns and border closures impacted medicine availability during the COVID-19 pandemic. This study aimed to assess the availability of essential, generic medicines for chronic diseases at public pharmaceutical supply agencies in Ethiopia.Design Comparative cross-sectional study.Setting The availability of essential, generic medicines for chronic diseases was assessed at two public pharmaceutical supply agency hubs.Participants The current study included public supply agency hub managers, warehouse managers and forecasting officers at the study setting.Outcomes The assessment encompassed the availability of chronic medicines on the day of data collection, as well as records spanning 8 months before the outbreak and 1 year during the pandemic. A total of 22 medicines were selected based on their inclusion in the national essential drug list for public health facilities, including 17 medicines for cardiovascular disease and 5 for diabetes mellitus.Results The results of the study indicate that the mean availability of the selected basket medicines was 43.3% (95% CI: 37.1 to 49.5) during COVID-19, which was significantly lower than the availability of 67.4% (95% CI: 62.2 to 72.6) before the outbreak (p<0.001). Prior to COVID-19, the overall average line-item fill rate for the selected products was 78%, but it dropped to 49% during the pandemic. Furthermore, the mean number of days out of stock per month was 11.7 (95% CI: 9.9 to 13.5) before the outbreak of COVID-19, which significantly increased to 15.7 (95% CI: 13.2 to 18.2) during the pandemic, indicating a statistically significant difference (p<0.001). Although the prices for some drugs remained relatively stable, there were significant price hikes for some products. For example, the unit price of insulin increased by more than 130%.Conclusion The COVID-19 pandemic worsened the availability of essential chronic medicines, including higher rates of stockouts and unit price hikes for some products in the study setting. The study’s findings imply that the COVID-19 pandemic has aggravated already-existing medicine availability issues. Efforts should be made to develop contingency plans and establish mechanisms to monitor medicine availability and pricing during such crises.